Energy Transition in the GCC: From Oil Giants to Green Leaders? - Jihen Bousrih; Manal Elhaj (Energies, 2025)
During the 28th Conference of the Parties (COP28), organized under the United Nations Framework Convention on Climate Change and hosted by the United Arab Emirates, member nations reached a global agreement to begin transitioning away from fossil fuel dependence, forcing the Gulf Cooperation Council (GCC) countries to balance their commitment to a green transition with the need to secure short-term energy supplies. This study highlights the challenges facing the GCC’s efforts to expand renewable energy, even as the region continues to have a significant influence over international energy markets. This study utilizes dynamic panel estimation over the period 2003 to 2022, focusing on the core pillars of the Energy Transition Index to analyze the evolving renewable energy use in the GCC. The results present a clear and optimistic perspective on the region’s renewable energy prospects. Despite the continued dependence on fossil fuels, the findings indicate that, if effectively managed, oil and gas revenues can serve as strategic instruments to support the transition toward cleaner energy sources. These insights offer policymakers robust guidance for long-term energy planning and highlight the critical importance of international collaboration in advancing the GCC’s sustainable energy transition.